Promoting Traditional Cultural Expressions via YouTube - Laina Rafianti; Ahmad M. Ramli; Rika Ratna Permata (Faculty of Law, Universitas Jenderal Soedirman, 2019)
YouTube is a potential media to promote Indonesian traditional cultural expressions in Indonesia. Even though the promotion of traditional cultural expressions is growing fast, the communal intellectual property law is still a big question mark. The purposes of this paper are, first, to identify how YouTube impact on utilizing Indonesian culture, to analyze how to gain economic benefit from broadcasting through YouTube, and to note how to balance rights and obligations between traditional cultural expressions stakeholders. From a methodological standpoint, this paper used both a normative and ethnography-legal research approach. This paper result is, first, YouTube gives influence directly and indirectly to the promotion of traditional cultural expressions; and second, custodian and performers of traditional cultural expressions potentially receive the economic benefit from broadcasting through YouTube. Ultimately, petahelix approach is required in obtaining a balance right and obligation between traditional cultural stakeholders.Keywords: YouTube, Traditional Cultural Expressions, Intellectual Property, Copyright